Learning the Yellow Book of Nubdatul Bayan in the Acceleration Program at the Mambaul Ulum Al-Hamidiyah Foundation Mayang Jember - Zairotin Najah R; Moh. Khusnuridlo; Fathiyaturrahmah (Syntax Corporation Indonesia, 2023)
The yellow book learning among the people is no longer a stranger, because many people have lodged their children in Islamic boarding schools so that they can learn the yellow book learning. The mambaul ulum al-hamidiyah foundation is one of the foundations that applies the learning of the nubdatul bayan yellow book in the acceleration program. Where acceleration means acceleration and the book of nubdatul bayan is one of the books that teaches how to quickly read a book that discusses the science of tools, namely the science of nahwu and the science of sorrof. This study aims to determine how the planning, implementation and evaluation. This research uses descriptive qualitative method with the type of field research (field research). The results of this study indicate that the Book of Nubdatul Bayan Learning Planning in the Acceleration Program follows the curriculum that has been provided in detail by the center, and the rest for the RPP the clerics / clerics add themselves according to the learning material. The implementation of the Nubdatul Bayan Book Learning in the Acceleration Program has three important activities, namely introduction, core activity, and closing. In terms of Evaluation of the Learning of the Book of Nubdatul Bayan in the Acceleration Program, there are two tests, namely: a written test and an oral test.